"All the world's a shopping cart": Theorizing the political economy of ubiquitous media and markets. (December 2015) - McGuigan, Lee; Manzerolle, Vincent
Ubiquitous connectivity to networked information-communication technologies increasingly mediates social experiences of markets and retail environments. These conditions lead some marketing scholars to conclude that digital media are reaching their inevitable culmination: an omnipresent marketplace. They call this "ubiquitous commerce" (u-commerce). U-commerce annihilates constraints over markets; borders, cultural differences, and geography cease to impose friction on exchange. As part of a broader understanding of new media and marketing, u-commerce deserves attention from critical communication studies. In foregrounding concerns of space, time, and consciousness, u-commerce exemplifies a commercial theory of media and invites critique at the nexus of medium theory and political economy. The work of Harold Innis is uniquely suited to this task. This article contextualizes and identifies biases in the conceptual systems and infrastructures of u-commerce.